Chilaiditi syndrome: A rare case report - Salma Salman; Faraz, Rehlish; Aslam, Shayan; Siddiqui, Afshan; Ahmed, Iftekhar (Journal of the Pakistan Medical Association, 2025)
Due to advancements in radiology, incidental findings are becoming more frequent, making it easier to diagnose rare conditions. Chilaiditi syndrome is one such rare condition, observed in only 0.28% of individuals. We report the case of an 84-year-old female who presented to a tertiary care setup with complaints of severe abdominal pain and vomiting. On examination, her abdomen was more tender in the right upper quadrant, and gut sounds were sluggish. A nasogastric tube was passed, which revealed greenish aspirate. The surgical team was consulted, however, the patient was admitted under medical services for conservative management. A CT scan revealed the interposition of the transverse colon between the liver and diaphragm, a rare finding characteristic of Chilaiditi syndrome. The patient showed improvement with conservative management and was discharged from the hospital. Physicians and surgeons must remain aware of the rare possibility of Chilaiditi syndrome, as unawareness may lead to unnecessary surgical interventions for patients. Key Words: Chilaiditi syndrome, Chilaiditi sign, Colon.